Who is selling you chiquilitros of gasoline? Evidence from a public disclosure policy - Santiago Guerrero (Banco de México, 2012)
This paper estimates the impacts of disclosing information online and through the newspapers of gas stations that violate fuel supplying standards in Mexico. Using data from inspection histories, it finds that disclosing information online decreases the probability that any gas station would be found in violation in subsequent periods. Gas stations exposed in the newspapers are estimated to decrease their sales at the month of the newspaper publication. This effect fades with time and is not significant for subsequent months. The paper shows that public disclosure mechanisms can complement enforcement effort in contexts where institutions are weak.
Keywords: K42; K32; L51; 330; Public disclosure; Corruption; Enforcement; Inspections; Violations